Adjektiva Komparatif (Silih Kata) Teks Persuasif Mahasiswa Pendidikan Bahasa dan Sastra Indonesia Universitas Negeri Makassar - Azis Azis; Juanda Juanda (Seminar Nasional LP2M UNM, 2019)
Choose comparative adjectives as a fundamental problem in persuasive texts. Disclosure of each sentence with the method used content analysis. Data sources were persuasive texts of Indonesian Language and Literature Education students, Faculty of Language and Literature, State University of Makassar, 2017. Data were collected using documentation techniques. Data were analyzed by transcribing first to explore the comparative alternating adjectives. The findings of this study indicate that comparative adultery is healthier than sick or less healthy; faster, slow, not fast; penance more conscious than the word unconscious; one word lighter than weight in it states a comparison which all show as comparative. Adjective word turns out to strengthen the persuasive text so that the reader is more intrigued to read and apply information obtained in the text; comparative adjective adjectives sometimes are followed by the use of instead, and sometimes not the word is followed, but it is implied.